Nuclear heme oxygenase-1 improved the hypoxia-mediated dysfunction of blood-spinal cord barrier via the miR-181c-5p/SOX5 signaling pathway. Issue 2 (13th January 2021) - Yu, Deshui; Sun, Rui; Shen, Dequan; Ge, Lihao; Xue, Tao; Cao, Yang
Abstract : Our previous study demonstrated that adenovirus-delivered GFP nuclear heme oxygenase-1 (nuclear HO-1, NHO-1) fragments lacking 23 amino acids at the C-terminus (Ad-GFP-HO-1C[INCREMENT]23) showed the potential therapeutic effects mediated by its improvement of the blood-spinal cord barrier (BSCB) integrity. However, the NHO-1-mediated molecular mechanism in regulating the BSCB function remains unclear. The BSCB model in vitro was established via a coculture of primary rat brain microvascular endothelial cells (RBMECs) and spinal cord astrocytes on transwell system. NHO-1 markedly reduced the disruption of the BSCB integrity induced by hypoxia. And NHO-1 significantly attenuated the expression of miR-181c-5p, but increased the expression level of SOX5 protein. miR-181c-5p was shown as an essential miRNA for increasing the BSCB permeability under hypoxia condition. Furthermore, we identified that miR-181c-5p could regulate the expression of SOX5 through binding to the 3′-UTR of its mRNA. And the decreased BSCB permeability and upregulation of tight junction (TJ) protein expression induced by NHO-1 could be partly reversed by the inhibition of SOX5 or miR-181c-5p (+). The present study results provide a better understanding of the molecular mechanisms induced by NHO-1 in improving the BSCB integrity, which is associated with the regulation of miR-181c-5p/SOX5/TJ signaling pathway. Abstract : Supplemental Digital Content is available in the text.